Gestão de redes: a arte da geração de novos benefícios - Alves, Juliano Nunes (2011)
The challenge of this work is to deepen the knowledge, expand the domain, to provide a deeper analytical view on the issue concerning to generation of benefits for interorganizational networks and the direction of the new benefits in an increasingly competitive environment by creating new interorganizational networks and also by uncertainty about the expectations of participants throughout the relationship. In some cases, also presents the individualistic behavior, where there is no sharing of knowledge and also the stable behavior, observed in certain interorganizational networks. Therefore, a study about the benefits contributes to the interorganizational networks conducive to its participants a competitive power and relevance in the market, capable of overcoming the limits of each individual member and thus be able to seek help for your business to flourish, grow and fruit. The method used for this project was an exploratory survey research, and relying on the qualitative and quantitative analysis. This, because of the analysis, interpretation and presentation of data will be valid, at certain moments, of numerical data, applying univariate statistics and multivariate statistics, and in others, by interpretative aspects of the interviews. In the results we can see that, regarding the establishment and management of networks, it appears that this process occurs similarly among the networks studied, thereby demonstrating that the initial benefits are not sufficient to maintain competitive advantages, because competing networks to be formalized by the same initial benefits. At the end of this work, from the results presented, we can answer the last specific objective: To identify the direction of the new benefits for interorganizational networks. The direction of the new benefit was shown from both the interviews and the results of quantitative analysis, the networks are becoming increasingly concerned about their development process through exchange of experiences and knowledge, which from these interactions will get new ideas and new benefits to achieve it with greater legitimacy in the market and therefore greater sustainability. This concern has shown that the Brazilian interorganizational networks to achieve greater competitiveness in their market, they should be qualified for a more dynamic exchange of information and knowledge.